Pathways to Psychiatric Help among Tribal Patients with Mental Disorders in India - Chittaranjan Subudhi; Ramakrishna Biswal; Abhijit Pathak (Indian Journal of Psychiatric Nursing)
Background: The pathways of mental illness treatments are mostly uncertain. Previous studies have agreed on sociodemographic and cultural factors in determining a patient’s and their family’s health-seeking pathways. Methods: However, the present study aims to understand the health-seeking pathways of less explored tribal population and their path of resorting to medical professionals. Fifty tribal patients were selected from the Department of Psychiatry, Ispat General Hospital, Rourkela, Odisha, India, through a convenience sampling technique. A structured interview schedule was used to record the respondent’s responses. Results: Results came up with 90% of tribal patients visit medical professionals for a speedy recovery, whereas 82% of patients and their families believe in the easy availability of traditional healers, and 55% think that allopathy is unsuccessful in treating mental illness. Conclusions: Thus, it makes traditional healers the first choice of treatment. Future studies should try to bring traditional and medical practitioners under one roof to ascertain the patient recovery rate and contribution in removing patient’s load from tertiary care.